Feeding Behaviour of Peranakan Ongole (PO) Cattle in Block Merak Resorts Labuhan Merak Baluran National Park Jawa Timur - Hidayat Teguh Wiyono; Eva Tyas Utami; Ahmad Alfan Abdullah (Universitas Sam Ratulangi, 2022)
Feeding behaviour is an essential activity that is done by the animals to obtain the nutrition. The objective of this study was to investigate feeding behaviour Peranakan Ongole (PO) cattle’s include the frequency and duration of foraging, grazing and ruminating time. The study used five of more than 2 years old PO cattle females which are not pregnant or breastfeeding. The observation was done by focal animal sampling method and recorded by using continuous recording method for seven days in a row. The result of the research indicated that cattle’s feeding behaviour in Block Merak Resorts Labuhan Merak when it was shepherded at noon in Savannah has a highest frequency foraging, grazing and ruminating in 8 hours constantly was done by A cattle in 9.44 times. The lowest frequency of foraging, grazing and ruminating in 8 hours constantly was done by D cattle in 0.85 times. The longest duration of foraging, grazing and ruminating in 8 hours constantly was done by C cattle in 267.05 minutes. The shortest duration of foraging, grazing and ruminating in 8 hours constantly was done by C cattle 16 minutes. The conclusion of this research is that feeding behavior patterrn of semi intensive farming system PO cattle’s in Block Merak is: foraging-grazing-ruminating and foraging-grazing. Based on the average score of each individual, grazing is the mostfrequent that is done by PO cattle’s is 9.18 times and 246.34 minutes. Whereas, ruminating is the least feeding activity is 0.91 times and 2.22 minutes.Keywords: feeding behavior; PO cattle; Baluran National Park ABSTRAK Perilaku makan merupakan kegiatan penting yang dilakukan oleh hewan untuk mendapatkan nutrisi. Penelitian ini bertujuan untuk mengetahui perilaku makan sapi Peranakan Ongole (PO) meliputi frekuensi dan lama mencari makan, waktu merumput dan waktu ruminasi. Penelitian ini menggunakan lima ekor sapi PO betina berumur lebih dari 2 tahun yang tidak bunting atau menyusui. Pengamatan dilakukan dengan metode focal animal sampling dan dicatat dengan menggunakan metode continuous recording selama tujuh hari berturut-turut. Hasil penelitian menunjukkan perilaku makan sapi di Resor Blok Merak Labuhan Merak saat digembalakan pada siang hari di Savannah memiliki frekuensi mencari makan, merumput, dan ruminasi tertinggi dalam 8 jam secara konstan dilakukan oleh sapi A sebanyak 9,44 kali. Frekuensi mencari makan, merumput dan ruminasi terendah dalam 8 jam terus-menerus dilakukan oleh sapi D sebanyak 0,85 kali. Durasi mencari makan, merumput, dan ruminasi terlama dalam 8 jam terus-menerus dilakukan oleh sapi C dalam waktu 267,05 menit. Lama mencari makan, merumput dan ruminasi tersingkat dalam 8 jam terus-menerus dilakukan oleh sapi C 16 menit. Pola perilaku makan sapi PO sistem peternakan semi intensif di Blok Merak adalah: mencari makan-menggembala-merumput dan mencari makan-menggembala. Berdasarkan skor rata-rata tiap individu, penggembalaan paling sering dilakukan oleh sapi PO dalam waktu 9,18 kali dan 246,34 menit. Sedangkan ruminasi merupakan aktivitas makan yang paling sedikit yaitu 0,91 kali dan 2,22 menitKata kunci: perilaku makan; sapi PO; Taman Nasional Baluran